Dynamic Friction Behavior of Paper-Based Wet Friction Material Subjected to Contact Pressure Fluctuation - Yasuhisa Hattori; Yusuke Kato (Tribology Online, 2012)
In this research, dynamic friction behavior of paper-based wet friction material subjected to contact pressure fluctuation was investigated experimentally and theoretically. Complex friction coefficient obtained by the ratio between dynamic components of friction and normal force was defined as an index of dynamic friction characteristics. First, the frequency dependence of complex friction coefficient was measured changing the contact surface dimension and compressive modulus of specimen as parameters. As a result the amplitude and phase angle of complex friction coefficient decreased with the increase of pressure fluctuating frequency and this tendency was significant for larger dimension and for lower modulus. Then, calculations were done combining the stress-strain analysis with an analytical model based on the theory of poroelasticity and the assumption in which the solid part at contact surface only contributed to friction. It was found that the increase in load sharing ratio by fluid caused by the flow resistance made the solid contact relaxed and delayed, which resulted in the decrease in amplitude and phase angle of complex friction coefficient. The calculated results showed similar tendency to the experimental ones, thereby the analytical model was appropriate and the mechanism of dynamic friction behavior of paper-based wet friction material was demonstrated.